Five new replacement names in Reduviidae (Heteroptera) - Swanson, Daniel R. (Zootaxa, 2017)
The following five new replacement names are proposed for homonymous genus- and species-level names in four different subfamilies of Reduviidae: Dithectocoris nom. nov. for Echinocoris Livingstone & Ravichandran, 1992 nec Echinocoris Miller, 1949 (Ectrichodiinae); Sphedanolestes picturellus tordoi nom. nov. for Sphedanolestes picturellus annulipes Tordo, 1969 nec Sphedanolestes annulipes Distant, 1903 (Harpactorinae); Acanthaspis celidota nom. nov. for Acanthaspis maculata Sucheta & Chopra, 1989 nec Acanthaspis maculata (Distant, 1903); Reduvius lasius nom. nov. for Reduvius villosus Fabricius, 1794 nec (Thunberg, 1783) (Reduviinae); and Oncocephalus enallus nom. nov. for Oncocephalus bipunctatus Livingstone & Ravichandran, 1990 nec Oncocephalus bipunctatus Villiers, 1952. The genus-level replacement also results in Dithectocoris coromandelensis (Livingstone & Ravichandran, 1992) comb. nov.